Asnad, qat'namah-ha, qarardad-ha va payam-ha-yi chahar kungirah-'i Sazman-i Fada'iyan-i Khalq-i Iran (Aksariyyat) : (Intisharat-i Sazman-i Fada'iyan-i Khalq-i Iran (Aksariyyat), 1995)
'Documents, declarations, treaties and messages of the fourth congress of Fada'iyan Khalq Organization'